The Importance of Training Needs Assessment on E-Education in Government Schools in Basra - al-Jassem, Raghad saleh Darweesh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this paper, the relevance of Training Need Assessment (TNA) is examined in relation to the introduction of e-learning in government schools in Basra. E-education, or the use of digital technology to enhance learning, is becoming more and more common in educational facilities all over the world, including Basra. To close the digital gap and assure the adoption of e-education, it is crucial to understand the specialized training requirements of teachers and students. A mixed method was used in the study to obtain quantitative data and qualitative information from teachers and school officials. The teaching staff's present levels of e-education knowledge, abilities, and attitudes were evaluated using a properly crafted checklist questionnaire. In addition, interviews were performed to learn more about the difficulties in adopting e-education and to find viable solutions. The study's findings showed shortage in the training required for implementing e-education, indicating a major gap in the training needs assessment. The evaluation identifies numerous critical areas that need immediate attention and focused training activities, including digital literacy, content production, managing virtual classrooms, and utilizing technology for individualized learning. In addition, educators raised concerns about the incorporation of e-education into the curriculum as well as the absence of institutional support and resources, which add to the gap that has been discovered. The consequences of these findings highlight the crucial role that training needs assessments play in determining how best to integrate e-education in Basra's public schools. The report advises the creation and execution of thorough training programs specifically designed to meet the needs of educators and administrators. It also offers legislative changes to solve resource and infrastructure issues, creating a favorable climate for the development of e-education.